Restless giant : the United States from Watergate to Bush v. Gore - Patterson, James T. (Oxford history of the United States., 2005)
James Patterson's Bancroft Prize-winning Grand Expectations, the penultimate volume in the Oxford History of the United States, was hailed by The New York Times as ""a spirited, sprawling narrative of American life"" and by The Wall Street Journal as ""a tour de force."" Now, in the finalchronological volume of this acclaimed series, Patterson again offers an authoritative and vibrant history of a turbulent period in American life. Restless Giant provides a crisp, concise assessment of the twenty-seven years between the resignation of Richard Nixon and the election of George W. Bush, in a sw